An integrated system for assessing stroke risk - Kyriacou, Efthyvoulos C.; Pattichis, Constantinos S.; Karaolis, Minas A.; Loizou, Christos P.; Christodoulou, Christodoulos; Pattichis, Marios S.; Kakkos, Stavros K.; Nicolaides, Andrew N. (My University, 2007)
The objective of this article is to present an integrated system for the assessment of risk of stroke based on two modules: 1) clinical risk factors and noninvasive investigations, and 2) carotid plaque texture analysis. The system supports the data collected from the Asymptomatic Carotid Stenosis and Risk of Stroke (ACSRS) natural history study that includes following data: 1) clinical, biochemical, and electrocardiographic risk factors associated with cardiovascular deaths, and 2) whether any independent risk factors can be used to identify a high-risk group for cardiovascular death. Furthermore, the carotid plaque texture analysis module supports the normalization, despeckling, segmentation, texture feature extraction, and classification of ultrasound plaque images.
Keywords: Risk analysis; Algorithm design and analysis; Knowledge representation; Ιntegrated system; Myocardium; Clinical risk factors; Noninvasive investigations; Carotid plaque texture analysis